Ky-2, a Histone Deacetylase Inhibitor, Enhances High-Salinity Stress Tolerance in Arabidopsis thaliana. (12th December 2015) - Sako, Kaori; Kim, Jong-Myong; Matsui, Akihiro; Nakamura, Kotaro; Tanaka, Maho; Kobayashi, Makoto; Saito, Kazuki; Nishino, Norikazu; Kusano, Miyako; Taji, Teruaki; Yoshida, Minoru; Seki, Motoaki
Abstract : Adaptation to environmental stress requires genome-wide changes in gene expression. Histone modifications are involved in gene regulation, but the role of histone modifications under environmental stress is not well understood. To reveal the relationship between histone modification and environmental stress, we assessed the effects of inhibitors of histone modification enzymes during salinity stress. Treatment with Ky-2, a histone deacetylase inhibitor, enhanced high-salinity stress tolerance in Arabidopsis. We confirmed that Ky-2 possessed inhibition activity towards histone deacetylases by immunoblot analysis. To investigate how Ky-2 improved salt stress tolerance, we performed transcriptome and metabolome analysis. These data showed that the expression of salt-responsive genes and salt stress-related metabolites were increased by Ky-2 treatment under salinity stress. A mutant deficient in AtSOS1 ( Arabidopis thaliana SALT OVERLY SENSITIVE 1 ), which encodes an Na + /H + antiporter and was among the up-regulated genes, lost the salinity stress tolerance conferred by Ky-2. We confirmed that acetylation of histone H4 at AtSOS1 was increased by Ky-2 treatment. Moreover, Ky-2 treatment decreased the intracellular Na + accumulation under salinity stress, suggesting that enhancement of SOS1-dependent Na + efflux contributes to increased high-salinity stress tolerance caused by Ky-2 treatment.